Evaluation of the Reproductive Performance, Body Proportions, Nutritional Value, and Biochemical Parameters of Achatina achatina - Tchowan, Guy Merlin; Toukala, Jean Paul; Ngoula, Ferdinand; Tchoumboué, Joseph (International Journal of Zoology, 2022)
To assess the effect of energy levels on the reproductive performance of African Land Snails, ninety young snails of one month of age, weighing between 1 and 1.5 g, of shell length between 15.5 and 23.85 mm and shell diameter between 12.60 and 16.85 mm and free from wounds or shell defects were divided into 3 groups of 5 snails each and 6 replicates in cages equipped with feeders and drinking troughs. Each treatment was randomly assignedto one of the experimental feeds with variable energy levels (2600, 2800, and 3000 kcal/kg) in addition to pawpaw leaves as a staple feed. The cultured substrates were watered daily, and the animals were monitored for a period of 24 months. The results showed that the shortest ages of onset of maturity as well as the highest number of spawns per treatment were observed in snails receiving 2600 kcal/kg of energy in the feed compared to other treatments. The highest egg morphometric and fertility characteristics were found in animals fed the highest energy level of the feed. The highest protein level in the hemolymph was observed in snails given 3000 kcal/kg energy of the feed while the lowest cholesterol level was observed in animals receiving the same treatment. The highest total meat and gonad weight were observed in animals receiving 2800 kcal/kg energy in the feed compared to other treatments. The levels of dry and organic matter, protein, and fat in the ash increased with the energy level of the diet. Animals that received 2800 kcal/kg energy in the diet recorded a significantly lower calcium level in the flesh compared to the other two treatments. On the other hand, the percentage of phosphorus increased significantly with the energy level of the diet. In conclusion, the 2600 kcal/kg energy level can be retained in the feed of adult snails.